Application of Weibull theory to laser surface textured Al2O3. Issue 2 (February 2021) - Liu, Chao; Aengenheister, Stefan; Herzog, Simone; Deng, Yuanbin; Kaletsch, Anke; Schmitz, Katharina; Broeckmann, Christoph
Abstract: The Weibull theory has been widely used to analyse the flexural strength and reliability of advanced structural ceramics. But it has a lot of limitations and must be applied with caution. Laser surface texturing (LST) has been well known to be capable of further improving the tribological performance and reduce the friction of ceramics. However, the influence of LST on the flexural strength has been scarcely researched. In this study, the Weibull theory is applied to dense-sintered fine Al2 O3 ceramic with polished and laser textured surfaces based on the biaxial ball-on-3-balls (B3B) test. It is found that by adapting the previous formula of B3B strength, considering the compressive residual stress and size effect induced by LST, the Weibull theory can be applied to investigate the influence of LST on the strength of Al2 O3 . Moreover, a necessary condition for very small specimens was developed to facilitate the usage of Weibull theory on brittle materials.